2004
DOI: 10.1080/10584580490894645
|View full text |Cite
|
Sign up to set email alerts
|

A Hydrothermally Deposited Epitaxial PbTiO3 Thin Film on SrRuO3 Bottom Electrode for the Ferroelectric Ultra-High Density Storage Medium

Abstract: A lead titanate epitaxial thin film is one of the important ferroelectric films and lattice matching with strontium titanate is preferable. However, it was thought to be difficult to obtain high insulation property and very few superior hysteresis curves were measured with lead titanate. The hydrothermal method can avoid a lead vacancy and residual strain at the boundary of the substrate due to low reaction temperature of 150• C. Using strontium ruthenium oxide bottom electrode on strontium titanate, the lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In-plane and out-of-plane lattice parameters of ( 1 out-of-plane lattice parameters, (a and c, respectively), against x in (1−x)BNT-xBKT films in this work together with the reported lattice parameters of (1−x)BNT-xBKT ceramics prepared by a conventional sintering technique. 22) The a lattice parameter of (1−x)BNT-xBKT ceramics increases slightly as x increases, while that of (1−x)BNT-xBKT films is almost a constant, which is well matched with the lattice parameter of SrRuO 3 films and SrTiO 3 (3.905 Å) 37) as can be seen from the RSMs shown in Fig. S2, indicating that the films are strongly clamped by SrRuO 3 films and SrTiO 3 substrates and exhibit coherent epitaxy.…”
Section: Crystal Structuresmentioning
confidence: 71%
“…In-plane and out-of-plane lattice parameters of ( 1 out-of-plane lattice parameters, (a and c, respectively), against x in (1−x)BNT-xBKT films in this work together with the reported lattice parameters of (1−x)BNT-xBKT ceramics prepared by a conventional sintering technique. 22) The a lattice parameter of (1−x)BNT-xBKT ceramics increases slightly as x increases, while that of (1−x)BNT-xBKT films is almost a constant, which is well matched with the lattice parameter of SrRuO 3 films and SrTiO 3 (3.905 Å) 37) as can be seen from the RSMs shown in Fig. S2, indicating that the films are strongly clamped by SrRuO 3 films and SrTiO 3 substrates and exhibit coherent epitaxy.…”
Section: Crystal Structuresmentioning
confidence: 71%
“…Thicker films are favorable for applications in piezoelectric microacuators and microsensors [46] . In the hydrothermal process, polarization is aligned automatically to achieve a 3D deposition [47] . The reaction temperature, pressure, and solution pH value are all important factors in controlling film properties, like composition and thickness.…”
Section: Hydrothermal Methodsmentioning
confidence: 99%
“…It may be noted that Morita et al have reported P r up to 96.5 C/cm 2 with a coercive field ∼290 kV/cm for highly epitaxial (0 0 1) PTO films grown on a SrRuO 3 /SrTiO 3 substrate by a hydrothermal process. 33 As PbTiO 3 doesn't exhibit the polarization rotation noted in morphotropic phase boundary PZT, we can estimate a value of P r in the (1 0 0) direction, by a simple projection onto the [0 0 1] axis resulting in P r (0 0 1) ≈ 73 C/cm 2 , approximately 25% less than Morita's value.…”
Section: Filmsmentioning
confidence: 97%